2022
DOI: 10.3389/fped.2022.915312
|View full text |Cite
|
Sign up to set email alerts
|

Automated Oxygen Delivery in Neonatal Intensive Care

Abstract: Oxygen is the most common drug used in the neonatal intensive care. It has a narrow therapeutic range in preterm infants. Too high (hyperoxemia) or low oxygen (hypoxemia) is associated with adverse neonatal outcomes. It is not only prudent to maintain oxygen saturations in the target range, but also to avoid extremes of oxygen saturations. In routine practice when done manually by the staff, it is challenging to maintain oxygen saturations within the target range. Automatic control of oxygen delivery is now fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“… 38 As such, improving the FiO 2 –SpO 2 relationship remains a persistent challenge in neonatal care. Recent efforts have been made to develop methods for reducing FiO 2 and SpO 2 variations, including automated control systems 39 and feedback systems. 40 Nevertheless, further research is still needed to understand the pathobiology of oxygen fluctuations better and to aid in developing effective strategies for minimizing their effects.…”
Section: Discussionmentioning
confidence: 99%
“… 38 As such, improving the FiO 2 –SpO 2 relationship remains a persistent challenge in neonatal care. Recent efforts have been made to develop methods for reducing FiO 2 and SpO 2 variations, including automated control systems 39 and feedback systems. 40 Nevertheless, further research is still needed to understand the pathobiology of oxygen fluctuations better and to aid in developing effective strategies for minimizing their effects.…”
Section: Discussionmentioning
confidence: 99%
“…1 Closed-loop automated oxygen control (CLAC) systems may provide a solution as their use in preterm infants has been associated with fewer desaturations, 2 increased percentage of the time spent within the target oxygen saturation range and fewer manual adjustments to the inspired oxygen concentration. 3,4 In the interim analysis of a randomised crossover trial of CLAC, we demonstrated that automated oxygen control had similar benefits in ventilated infants born at or above 34 weeks gestation. 5 In the interim analysis, most of our patients had a low oxygen requirement, we continued recruitment to the target sample…”
mentioning
confidence: 86%
“…Compliance of achievement of SpO 2 targets in preterm infants is low, especially in maintaining the SpO 2 below the upper limits of the target range and avoidance of hyperoxemia 1 . Closed‐loop automated oxygen control (CLAC) systems may provide a solution as their use in preterm infants has been associated with fewer desaturations, 2 increased percentage of the time spent within the target oxygen saturation range and fewer manual adjustments to the inspired oxygen concentration 3,4 . In the interim analysis of a randomised crossover trial of CLAC, we demonstrated that automated oxygen control had similar benefits in ventilated infants born at or above 34 weeks gestation 5 .…”
Section: Introductionmentioning
confidence: 93%
“…New technology has been developed enabling the contemporary neonatal ventilators to adjust the FiO 2 automatically (A-FiO 2 ) using different kind of algorithms to increase the time spent in the desired SpO 2 TR 12–14. Studies have shown that these A-FiO 2 systems are able to increase the time spent in the SpO 2 TR up to 75% of the time compared with manual control, with a decreased time spent in both hypoxaemia and hyperoxaemia 15 16.…”
Section: Introductionmentioning
confidence: 99%